Development of Ti–Nb and Ti–Nb–Fe beta alloys from TiH2 powders. (1st January 2019) - Chirico, C.; Tsipas, S.; Toptan, F.; Gordo, E.
ABSTRACT: Ti–Nb β alloys are a promising alternative as an implant material due to their good properties and low Young's modulus, compared to other Ti-alloys currently employed as biomaterials. In this study, three materials of the Ti–Nb and Ti–Nb–Fe systems were produced by powder metallurgy techniques starting from TiH2 (TH) powder. Several sintering cycles were employed to evaluate the H2 elimination and the effect of sintering temperature on densification and fraction of β -Ti phase. Also, the influence of alloying element size using two kinds of Fe powder was evaluated. The highest loss of H2 was achieved by decreasing heating rate at the temperature range of hydride decomposition. SEM images and XRD results show mainly a β -Ti phase for TH–40Nb and TH–5Fe–25Nb samples. The TH–12Nb sample shows ( α + β ) microstructure. Fe addition with smaller particle size seems to improve the diffusion of Nb into Ti which promotes a higher β -phase fraction and sample homogeneity.